TECHNOLOGY TO IMPROVE THE QUALITY OF LIFE FOR STUDENTS AT THE DOMYADHU PEJATEN - Rima Tamara Aldisa (Adisam Publisher, 2024)
The use of technology in education has become an important topic in improving the quality of life of students in various educational institutions, including orphanages. This research aims to explore how the application of technology can improve the quality of life of students at the Domyadhu Pejaten Jakarta. The method used in this research is a qualitative approach, through direct observation, in-depth interviews with orphanage administrators, teachers and students, as well as documents for analysis to collect data about existing conditions and the application of technology that has been carried out. The research results show that the use of technology, such as computers and internet access, online learning platforms, and educational applications, has a positive impact on the student learning process. Students' ability to access information and learning materials becomes wider, interaction between students and teachers through increased use of communication technology, and students' learning motivation appears to have increased. Apart from that, technology also helps in managing orphanage administration more efficiently. In conclusion, the application of technology at the Domyadhu Pejaten has good and significant potential to improve the quality of life of students.